The relationship between reactive strength measures and sprinting performance - Healy, R.; Smyth, C.; Harrison, A. J. (ISBS Proceedings Archive (Michigan), 2017)
This study examined the relationships between reactive strength measures and sprint performance. Ten female sprinters performed bilateral vertical hops and drop jumps (DJs) from 0.3 m and 40 m sprints. Ground contact time, flight time, height jumped and the reactive strength index (RSI) were calculated during hops and drop jumps. Sprint times over 10, 20, 30 and 40 m were also assessed. High positive correlations, calculated using Pearson`s r correlations, were found between Hop RSI and DJ RSI (r = 0.672) with no other significant correlations found. Although RSI values in hopping and drop jumping are related they should not be used interchangeably as they represent somewhat distinct reactive strength qualities. The results suggest that RSI values, calculated during hopping and drop jumping, were not related to sprint performance.